1997
DOI: 10.1021/jp963215x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Ice Electrolysis under UV Irradiation

Abstract: The type of photocharge carriers in ice was determined by means of an electrolysis technique. It was suggested earlier that irradiation of ice by UV light above 6.5 eV generates positive H3O+ ions, neutral OH• radicals, solvated electrons es -, D defects, and vacancies of water molecules according to the “autoionization” reaction. Is the photoconductivity (PC) observed purely “protonic”, due to motion of H3O+ ions and D defects, or does it have an additional electron component related to the motion of solvated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…The proton migration distance is about two water molecules in ice at ∼54 K and increases to about six molecules at 100 K. A sizable portion of hydroniums survive for an extraordinarily long time even at 140 K, probably due to the deficiency of OH − in comparison to H 3 O + in the ice sample. We consider the UV-induced formation of hydroniums to be consistent with observations from previous photoionization studies, including the enhanced electrical conductivity of UV-irradiated ice 5,6,8 and the occurrence of the H/D exchange reaction in ice. 23 Further, we suggest the possibility that metastable hydroniums play an important role in the acid-base chemistry of ice in UV-irradiated environments.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The proton migration distance is about two water molecules in ice at ∼54 K and increases to about six molecules at 100 K. A sizable portion of hydroniums survive for an extraordinarily long time even at 140 K, probably due to the deficiency of OH − in comparison to H 3 O + in the ice sample. We consider the UV-induced formation of hydroniums to be consistent with observations from previous photoionization studies, including the enhanced electrical conductivity of UV-irradiated ice 5,6,8 and the occurrence of the H/D exchange reaction in ice. 23 Further, we suggest the possibility that metastable hydroniums play an important role in the acid-base chemistry of ice in UV-irradiated environments.…”
Section: Discussionsupporting
confidence: 78%
“…There are several reports on the occurrence of the indirect photoionization of ice at lower photon energies. Petrenko et al 5,6,8 observed enhanced electrical conductivity of ice during UV irradiation at an energy as low as 6.5 eV. They proposed that the UV irradiation generates H 3 O + in the ice as positive charge carriers responsible for the observed photoconductivity, along with photoelectrons, OH radicals, and various defects (Reaction (R5)):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the rigidity of the molecules excludes the possibility of vibrational energy transfer to intramolecular vibrational modes and reactions involving bond breaking in H 2 O molecules not initially photodissociated. Nor can the 'solvated electron' observed after UV irradiation of liquid water and ice [17][18][19][20] be treated explicitly. The initial ice configuration obeys the ice rules [21] and has a zero dipole moment.…”
Section: The Ice Modelmentioning
confidence: 99%
“…Generally, atmospheric icing is the deposition of frozen water on surfaces at or below freezing which may result of rain, freezing rain, wet snow, fog, supercooled clouds or vapour, or from spray or splashing water. Ice adhesion produces numerous troubles in many areas of human activity such as transportation, power transmission and distribution, aircraft, wind turbine blades, ships, and bridges [27]. Icing of power transmission lines during winter storms is a persistent problem that causes outages and costs millions of dollars in repair expenses [28].…”
Section: Ice Adhesion Mechanismsmentioning
confidence: 99%